Tindak Tutur Ilokusi Dalam Cuitan Twitter Cawapres Gibran Rakabuming Raka Dalam Masa Kampanye Kontestasi Pilpres 2024 - Clareta Rosintya Ardini; Rifda Nabila; Riska Meliyana; Ratri Nindya Agustina; Nadya Ihsanita; Asep Purwo Yudi Utomo; Ruly Indra Darmawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article discusses the use of language in communication, specifically focusing on the concept of pragmatics and expanding it to understanding the meaning behind words. This highlights the importance of considering the context in which language is used, as well as the intention of the speaker, to fully understand the message conveyed. This article aims to describe illocutionary speech acts in tweets on the Twitter account of vice presidential candidate Gibran Rakabuming Raka during the 2024 presidential election contestation campaign. This research is a type of qualitative descriptive research, with data in the form of tweets. This research shows the existence of illocutionary speech acts in several tweets on the Twitter account @gibran_tweet. The data collection technique in this research uses the note-taking technique. The research results found that there were 26 illocutionary speech acts with details of 7 assertive speech acts, 5 directive speech acts, 4 expressive speech acts, 6 commissive speech acts, and 4 expressive speech acts. The benefits of this research can be used as a reference for further relevant research.